In Pursuit of Utopia: “A Pakistani, an Arab and a Scotsman ‘Return’ to Cyprus…” - Kyriakides, Christopher (Études helléniques / Hellenic Studies, 2008)
This paper explores the role of aspiration in the formation of migrant experience, and argues that sparks of utopia are inherent to the human migratory process. A relationship between racism and anti-utopianism is drawn out in the tentative formation of a theory of migrant reception. Drawing on personal experience of transnational migration, the author narrates an ethnographic journey from second-generation migrant born and raised in Scotland of Greek Cypriot parents, to his recent 'return', illustrating that rejection of identity proliferation – the antithesis of conservative multiculturalism – can be experienced as liberatory. Personal narrative is situated within a wider socio-political analysis of modernity's shifting public-private divide, the contours of which are played out in the post-cold war demise of Left-Right ideological contest. The author contends that a politics of identity proliferation (multiculturalism) compliments the current capitalist dystopia, and concludes by arguing for a new utopian vision.